The Diabetes Disparity and Puerto Rican Identified Individuals: A Systematic Literature Review. (April 2017) - Johnson, Jalil A.; Cavanagh, Stephen; Jacelon, Cynthia S.; Chasan-Taber, Lisa
Purpose: The purpose of this systematic review was to describe what is known about the diabetes disparity affecting Puerto Rican identified adults living in the continental United States as well as illuminate areas that merit further investigation. Methods: The CINAHL and PubMed databases were searched using the keywords Hispanic, Puerto Rican, and type 2 diabetes . Search limits included < 10-year-old, peer-reviewed, systematic reviews, available in the English language. The abstracts of 124 articles were reviewed, and 7 articles were reviewed in depth. Results: The Puerto Rican identified Hispanic subgroup is disproportionately affected by diabetes—the diabetes disparity. Puerto Rican identified Hispanic adults are less affected by citizenship status, may be less affected by English proficiency, use health care services differently, and have contextually different fatalistic views of diabetes compared with other Hispanic identified people. Spiritual/religious influences, associated mental health problems, and general cultural practices related to diabetes self-care are understudied in this group. Conclusion: Ambiguous use of the term Hispanic should be avoided when describing Hispanic subgroups. Stronger, more robust studies are needed to understand the unique cultural forces influencing the poor diabetes outcomes and individual behaviors that contribute to generally suboptimal diabetes self-care for Puerto Rican adults with type 2 diabetes.